2011
DOI: 10.4187/respcare.01096
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival in Patients With Tracheostomy and Prolonged Mechanical Ventilation in Olmsted County, Minnesota

Abstract: BACKGROUND An increasing number of patients require prolonged mechanical ventilation (PMV), which is associated with high morbidity and poor long-term survival, but there are few data regarding the incidence and outcome of PMV patients from a community perspective. METHODS We retrospectively reviewed the electronic medical records of adult Olmsted county, Minnesota, residents admitted to the intensive care units at the 2 Mayo Clinic Rochester hospitals from January 1, 2003, to December 31, 2007, who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
4
19
1
1
Order By: Relevance
“…Meanwhile, high-volume physicians in high-volume hospitals are most likely to achieve good outcomes for patients because such physicians are usually assisted by highly skilled and interdisciplinary care teams. [23][24][25] Predictors of in-hospital mortality identified in the current study included CCI and LOS, similar to the findings in other previous reports of ANN models for predicting patient mortality. 7,25 Morbid patients receiving mechanical ventilation are typically burdened by a host of comorbid conditions related to mechanical ventilation that increase their risk of medical complications.…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, high-volume physicians in high-volume hospitals are most likely to achieve good outcomes for patients because such physicians are usually assisted by highly skilled and interdisciplinary care teams. [23][24][25] Predictors of in-hospital mortality identified in the current study included CCI and LOS, similar to the findings in other previous reports of ANN models for predicting patient mortality. 7,25 Morbid patients receiving mechanical ventilation are typically burdened by a host of comorbid conditions related to mechanical ventilation that increase their risk of medical complications.…”
Section: Discussionsupporting
confidence: 88%
“…Of the 23 patients (7.1%) who were discharged home, 22 (96%) did not have an infection. The percentage of patients discharged home (7.1%) was lower than that reported in other studies, 33,34 a finding that may be attributed to a higher severity of illness in our sample. Compared with patients who had infection after tracheostomy, the percentage of patients discharged to a rehabilitation facility was higher for patients who had no infection or who had infection before the tracheostomy.…”
Section: Discussioncontrasting
confidence: 83%
“…1 The study confirmed that approximately 10% of patients with invasive mechanical ventilation undergo tracheotomy and that overall 1-year mortality in that population is still substantial. Older age and the presence of COPD negatively impacted survival, whereas survival was better among neuromuscular patients who continued to receive mechanical ventilation even after discharge.…”
supporting
confidence: 54%